Vegetation Structure along an Altitudinal Gradient in Phakot Watershed in Garhwal Himalaya, Uttarakhand, India - Dar, Tanweer A.; Habib, Bilal; Khan, Jamal A. (Indian Forester, 2010)
The paper deals with the variation of the vegetation along an altitudinal gradient in the Phakot Watershed - mosaic of civil and reserve forest inhabited by more than 20 hamlets. Phakot Watershed Area (PWA) is a part of Phakot beat of Saklana range of Garhwal Himalaya. The vegetation of the Phakot falls under Himalayan temperate forest. Tree cover (F = 6.189, P < 0.000) and shrub cover (F = 9.313, P < 0.000), varied significantly across different habitat types. Tree cover was highest at middle altitude. Quercus leucotrichophora was the dominant tree species (lVI 98.6) and contributed 31 % to the total density of PWA. Aspect also showed variation in terms of density, diversity and richness of trees and shrubs in the PWA. Cluster analysis separated agriculture land as the most dissimilar habitat mainly because oflack oftree species. Phakot, being one of the micro-watershed areas of the Garhwal Himalaya, but its strategic location with respect to outer and inner Himalaya explained the gradation of the vegetation wi th respect to altitude and aspect.